The role of pleomorphic adenoma stroma on its neoplastic progression: state of art - Rocha, Flávia Godinho Costa Wanderley; Araújo, Roberto Paulo Correia de; Martins, Gabriela Botelho; Medrado, Alena Ribeiro Alves Peixoto (Journal of Oral Diagnosis, 2018)
The tumor development is linked to its stroma. The study of tumor stromal cells enables the understanding of the neoplastic progression. The present narrative literature review aimed to describe tumor stromal cells, such as endothelial and inflammatory cells, that may induce the neoplastic progression of pleomorphic adenomas. The Latin American and Caribbean Center on Health Sciences Information (BIREME) and PubMed electronic databases were searched for scientific articles on this subject published in Portuguese and English from 2007 to 2017. The search focused on information about the clinical, imaging, and anatomopathological characteristics of pleomorphic adenomas and its neoplastic progression. After analyzing abstracts and reading the cataloged manuscripts, 44 articles were selected. It was shown that the tumor stroma is important for neoplastic progression by providing elastic properties to the tumor and by enabling its nutrition. Thus, it is relevant to study the cellular and molecular mechanisms that occur in extracellular matrix in order to understand the biological behavior of pleomorphic adenoma.